TRADITIONAL CHINESE BOOKBINDING FORMS AND THEIR INFLUENCE ON MODERN BOOK DESIGN - REN , Y.; DUBRIVNA, A. (Art and Design, 2024)
The purpose: to investigate and analyze the characteristics of ancient Chinese traditional book binding methods; explore the reasonable integration and innovative application of traditional elements in modern Chinese book design. Methodology is based on system-analytical, comparative, complex-historical methods, which made it possible to comprehensively investigate the specified problem and reach reasonable conclusions. The results. Based on the analyze of literature, a summary was made, and the traditional book-binding methods and characteristics of China in different periods were studied and analyzed. Such as bamboo and wooden strip books, scroll bookbinding, whirlwind bookbinding, accordion fold bookbinding, butterfly fold bookbinding, wrap back book binding, and thread-bound books. On this basis, the influence of traditional bookbinding on modern book design is analyzed, as well as the integration and application of traditional elements in modern book design. Scientific novelty. It is proposed the concept of integrating and innovating the application of traditional Chinese binding methods in contemporary book design. It is suggested combining modern technological means and materials to improve traditional binding methods, applying them reasonably in suitable book designs. This approach not only imparts unique cultural characteristics to contemporary Chinese book design but also provides academic support and theoretical guidance for the inheritance and development of traditional culture, promoting the integrated development of design and craftsmanship. Practical significance. To address the current crisis of the decline of traditional Chinese culture and the issue of homogenization in book design, this study analyzes and summarizes the traditional Chinese bookbinding methods. This not only provides a deeper understanding of the development of Chinese book design but also offers new perspectives and possibilities for contemporary book design. The study emphasizes the clever and reasonable application of traditional elements in design.